PENGARUH LOCUS OF CONTROL DAN SELF-EFFICACY TERHADAP KOMITMEN ORGANISASI PEGAWAI PADA BALAI LATIHAN KERJA (BLK) DI KOTA TERNATE - Marwan Marwan; Adnan Rajak; Anjas Mukti Yallo (Jurnal Manajemen Sinergi, 2018)
This research aims to determine the effect of partially and simultaneously variable locus of control and self-efficacy against Organizational Commitment On Office Training Center in Ternate City. The number of the target population as a whole is as much as 43 people. The amount is entirely used as a sample in this study. Model analysis used to test the hypothesis is multiple linear regression analysis, and SPSS as a statistical test. The study found that: (1) Locus of control positive and significant effect on organizational commitment. These results indicate that the the locus of control led to increased organizational commitment of employees in Ternate City Training Center, (2) Self-efficacy positive and significant effect on organizational commitment. This means that the higher self-efficacy lead to increased organizational commitment of employees at the Office Training Center of Ternate City, and (3) Locus of control and self efficacy together positive and significant impact on organizational commitment.